Geophysical investigation of effect of Aba-Eku public refuse dump site in Ibadan (South-West Nigeria) on groundwater quality. (2011)
Geophysical method was used to investigate the effect of Aba-Eku(N 07° 19.551 E 003° 59.027') public refuse dump site in Ibadan on groundwater quality. "Four vertical electrical sounding (YES) data from the vicinity of the dump site and one YES from the control point were acquired using Schlumberger electrode configuration which were subsequently processed and interpreted bazed on the assess of the iteralive computer model using a finite difference algorithm. The result showed that all the sides of the dump site have low resistivity values (side A, p= 22.3Ὠm; side B, p=31.8 Ὠm; side C, p=38.9Ὠm and side D, p=34.7Ὠm) compared with the resistivity value of the control point (Glory Tower Schools, p=60.6Ὠm). The low resistivity values around the ump site is an indication of groundwater pollution. This was confirmed by the laboratory water sample analysis from the vicinity of the damp site.